PERIDOTITE MELTING AND MINERAL-MELT PARTITIONING OF MAJOR AND MINOR ELEMENTS AT 22-24.5 GPA - Tronnes R.G.; Frost D.J. (My University, 2002)
Melting experiments at 2100-2400°C and 22-24.5 GPa to determine the liquidus to solidus phase relations and element partitioning coefficients were performed on different peridotite compositions: a pyrolite model and a KLB-1 composition. These starting materials, prepared as oxide mixes, were contained in Re capsules. The experiments were carried out using cubic-octahedral multianvil presses with 10/4 mm (octahedral edge length/anvil truncation edge length) and 18/8 mm pressure cell configurations with LaCrO3 heaters and axially inserted W-Re thermocouples. The 18/8 mm configuration with a stepped heater was developed in order to reduce the experimental thermal gradients. Some of the experiments were performed with Re-rod sample containers with two parallel chambers, allowing two different compositions to be run at identical conditions. Within experimental uncertainties, the melting relations of the KLB-1 and pyrolite compositions are identical in the 22-24.5 GPa range. Ringwoodite does not occur either in the melting range or just below the solidus, even at 22 GPa. Garnet (ga) and ferropericlase (fp) are the first liquidus phases at 22-23 GPa and at 24-24.5 GPa, respectively. The crystallization sequence is ga-fp-Ca-perovskite (cpv) at 22 GPa, ga-fp-perovskite(pv)-cpv at 23 GPa, and fp-pv-ga-cpv at 24-24.5 GPa. Major element distribution between the different phases implies that the solidus is approximately coincident with the appearance of cpv. The major element mineral-melt partitioning shows only minor variations with pressure in the investigated range. The mineral-melt KD(Fe/Mg)=(Fe/Mg)mineral/(Fe/Mg)melt decreases from 0.64 at 22-23 GPa to 0.62 at 24.5 GPa for ferropericlase and is below 0.46 for garnet and perovskite. The KD(Si/Mg) for garnet and perovskite decrease slightly from 1.34 at 22 GPa to 1.16 at 24.5 GPa. The Ca/Al ratio is elevated in the melt phase with mineral-melt KD(Ca/Al) for garnet and perovskite below 0.4. The partitioning coefficients indicate that partial melting or fractional crystallization in the transition zone and the uppermost part of the lower mantle will produce melts with elevated ratios of Fe/Mg and Ca/Al. The partitioning of minor elements like Ti, Cr, Ni and Na is strongly dependent on the proportions of the fractionating phases.
Keywords: PERIDOTITES; HIGH PRESSURE; MELTING; PEROVSKITE; GARNET GROUP; PERICLASE